The Effect of Nano Hydroxyapatite on the Bond Strength of Acrylic Teeth Repaired to an Acrylic Resin Denture Base Using Two Types of Auto Polymerized Acrylic Resins - Aziz, Hawraa khalid (Journal of Techniques, 2023)
The insufficiently binder between acrylic teeth and dentures is considered to be the primary cause of teeth fractures from the dentures and is one of the disadvantages of acrylic denture base material. This research has been conducted to assess various concentrations of Nano hydroxyapatite addition on the shear bond between repaired acrylic teeth and polymer. One-hundred specimens of resin were split into two main subdivisions. 50 specimens were repaired with cold cured Duracryl Plus and the other 50 were repaired with a special type of acrylic O-cry1. Each one was sectioned into tested groups depending on (1%., 2%., 3%, and 5% by wt. of nano hydroxyapatite) incorporation and control group (0% of nano hydroxyapatite) with (n=10). The Universal testing machine was utilized for shear bond strength measurement. The obtained values were diffracted by t-test, ANOVA, and LSD-test. There was an increase in bond strength that repairing with O-cry1 than Duracryl Plus with a heightening in the bond strength, which was seen with incorporating nano hydroxyapatite into the acrylic resin with a significant difference between them. The 2% wt. Nano hydroxyapatite group demonstrated the maximum mean values, while those for the 5% wt. Nano hydroxyapatite group were recording minimum value with a significant difference between them. Repairing with O-cry1 recording better bond strength than Duracryl Plus acrylic. Furthermore, the addition of hydroxyapatite in Nano-form has successfully improved the “shear bond strength” of teeth to the PMMA at 2% wt. nano hydroxyapatite.